SARANA DAN PRASARANA DALAM MEWUJUDKAN PROGRAM SEKOLAH RAMAH ANAK DI TAUD SAQU (TAHFIDZ ANAK USIA DINI) SUMENEP - Diva Az Zahra; Hanif Firdaus; Zainal Arifin Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study examines how the facilities and infrastructure at SaQu Sumenep Early Childhood Tahfidz Park (TAUD) contribute to the implementation of the Child Friendly School (SRA) program. The research used a descriptive qualitative approach, including interviews, observation, and documentation. The findings indicate that TAUD SaQu Sumenep has made significant efforts to provide facilities and infrastructure that support the SRA program, such as play areas, mini libraries, learning support facilities, and clean and comfortable learning spaces. However, there are some limitations, including budget constraints, limited accessibility of facilities, and the need to improve the quality of human resources. Overall, while TAUD SaQu Sumenep has met some of the SRA indicators, there is still room for improvement. The study concludes with recommendations for TAUD SaQu Sumenep to enhance the quality of facilities and infrastructure and strengthen the capacity of human resources to fully realize the SRA program.